Wind-Wise Automated Stability Analysis for Selection of Tower Crane and Location - Hebiba, Alaaeldin Magdy; Bouferguene, Ahmed; Moon, Sungkon; Han, Sanghyeok (Journal of Construction Engineering and Management, 2022)
Extreme wind speeds pose a serious threat to tower crane stability and can lead to excessive deflections or overturning of the mast. However, wind effects might not be considered directly in either the tower crane stability analysis or in the selection of a tower crane and use location. This problem may lead to crane failures or incidents due to extreme weather or improper selection of the crane foundation. To address these limitations, the present study proposes an automated system that includes: (1) mathematical models to determine the locations of the tower crane and the material supply, seeking to minimize not only lifting moments but also tower crane travel times; and (2) a static wind-based tower crane stability analysis to support the selection of a tower crane, which is the dimensions of its foundation that produce the most stable crane foundation system. A case study including 514 crane and material supply locations is adopted to validate the effectiveness of the proposed methodology.
Keywords: Crane model selection; Crane support reaction; Layout optimization; Mast deformation; Material supply; Model Selection; Site layout; Stability analyze; Support reaction; Tower crane site layout optimization; Crane model selection; Crane support reaction; Mast deformation; Tower crane site layout optimization; Wind effect